1998
DOI: 10.1104/pp.118.4.1455
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Salicylic Acid and Antioxidants during Induced Thermotolerance in Mustard Seedlings

Abstract: Heat-acclimation or salicylic acid (SA) treatments were previously shown to induce thermotolerance in mustard (Sinapis alba L.) seedlings from 1.5 to 4 h after treatment. In the present study we investigated changes in endogenous SA and antioxidants in relation to induced thermotolerance. Thirty minutes into a 1-h heatacclimation treatment glucosylated SA had increased 5.5-fold and then declined during the next 6 h. Increases in free SA were smaller (2-fold) but significant. Changes in antioxidants showed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
217
3
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(242 citation statements)
references
References 42 publications
17
217
3
5
Order By: Relevance
“…For example, generation and reaction of activated oxygen species (AOS), which causes the autocatalytic peroxidation of membrane lipids and pigments subsequently leads to membrane permeability and modification of its functions (Xu et al, 2006). Recent studies show that some signaling molecules may increase the antioxidant capacity of cells (Gong et al, 1997;Dat et al, 1998). Extreme temperatures led to accumulation of certain organic compounds termed osmolyte, including sugars, polyols, and proline.…”
Section: Discussionmentioning
confidence: 99%
“…For example, generation and reaction of activated oxygen species (AOS), which causes the autocatalytic peroxidation of membrane lipids and pigments subsequently leads to membrane permeability and modification of its functions (Xu et al, 2006). Recent studies show that some signaling molecules may increase the antioxidant capacity of cells (Gong et al, 1997;Dat et al, 1998). Extreme temperatures led to accumulation of certain organic compounds termed osmolyte, including sugars, polyols, and proline.…”
Section: Discussionmentioning
confidence: 99%
“…4A. Salicylic acid as an antioxidant activates ascorbate peroxidase, which, in turns, increases antioxidant ability and ascorbic acid amount in fruits (Dat et al, 1998;Wang et al, 2006). In addition, it has been shown that salicylic acid affects the biosynthesis and action of ethylene (Srivastava and Dwivedi, 2000), prevents vitamin C from being destructed (Wisniewska and Chelcowski, 1999) and acts as an anti-stress power (Elwana and El-Hamahmy, 2009).…”
Section: Titratable Acidity (Ta)mentioning
confidence: 99%
“…Efficient elimination of H 2 O 2 was possible due to the elevated GSH level in heat stressed mustard seedlings, which was facilitated by improved GR activity (Dat et al 1998). Higher GSH levels at the reproductive stage in apple plants enhanced their capacity for HT acclimation.…”
Section: Extreme Temperaturementioning
confidence: 99%